PARAGMATISME HUKUM ISLAM - Ahmat nijar (Institut agama islam negeri Padangsidimpuan, 2015)
Axiological values of Islamic law in practical-empirical level are key to measure the degree of benefit obtained. For that pragmatism Islamic law must always be given serious attention amid turnaround time and legal issues are increasing in quality and quantity. The theological foundation for this can be found in the passage and practices and the mujtahid mutaqaddimin friend.